The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-35982009001100026
|View full text |Cite
|
Sign up to set email alerts
|

Degradação ruminal e digestibilidade intestinal da proteína bruta de alimentos para bovinos

Abstract: RESUMO -Este trabalho foi conduzido com os objetivos de determinar as frações A e B e a taxa de degradação ruminal (Kd) da matéria seca (MS) e da proteína bruta (PB) de 27 alimentos e avaliar a digestibilidade intestinal da proteína não-degradada no rúmen pelas técnicas do saco de náilon móvel e de três estágios. Os alimentos avaliados foram farelos de arroz, babaçu, gérmen de milho e trigo; milho desintegrado com palha e sabugo, milho desintegrado com sabugo, milho, polpa cítrica, sorgo, amireia, farelos de a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
1
8
2
12
Order By: Relevance
“…The level of NDFap in cottonseed cake is similar to the one mentioned by Silva et al (2008b); this level was 46.30%. The sunflower meal level of 21.8% presented in the research of Marcondes et al (2009) is rather lower than the one observed in Table 1. Neutral detergent fiber directly influences voluntary consumption and nutritional value, as a result of its insolubility in neutral conditions, as the rumen, and in general, due to its slow utilization by ruminal microorganisms, in comparison with the components of the other feedstuffs (Detmann et al, 2008b).…”
Section: Resultscontrasting
confidence: 61%
“…The level of NDFap in cottonseed cake is similar to the one mentioned by Silva et al (2008b); this level was 46.30%. The sunflower meal level of 21.8% presented in the research of Marcondes et al (2009) is rather lower than the one observed in Table 1. Neutral detergent fiber directly influences voluntary consumption and nutritional value, as a result of its insolubility in neutral conditions, as the rumen, and in general, due to its slow utilization by ruminal microorganisms, in comparison with the components of the other feedstuffs (Detmann et al, 2008b).…”
Section: Resultscontrasting
confidence: 61%
“…A fração A encontrada para esse alimento foi inferior àquela comumente observada (Souza et al, 2000;Moreira et al, 2003;Oliveira et al, 2003;Cabral et al, 2005;Marcondes et al, 2009 Entre os subprodutos proteicos, a torta de soja e a torta de amendoim foram os que apresentaram maior potencial de substituição ao farelo de soja, pois suas degradações efetivas da matéria seca foram bem próximas à desse alimento.…”
Section: Resultsunclassified
“…A torta de amendoim apresenta alta variabilidade na degradação ruminal, e as frações A e B foram diferentes das descritas na literatura, de 58,02 e 36,43 (Marcondes et al, 2009), o que parece estar relacionado à própria variabilidade desse alimento no mercado. A falta de padronização desse subproduto no mercado pode influenciar significativamente os resultados da pesquisa.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O teor de proteína bruta é de aproximadamente 410g/kg de MS (Valadares Filho et al, 2010) e totalmente degradável no rúmen (Marcondes et al, 2009).…”
Section: Introductionunclassified